Achieving sustainable development goals in small and medium companies in Malaysia - Sarma Aralas (Asian Scholars Network, 2019)
This paper presents findings on the firm’s efforts to achieve sustainable development goals in its operations. A survey of small and medium sized manufacturing firms elicited responses from 67 companies on questions encompassing the seventeen sustainable development goals as defined by the United Nations. Small and medium sized Malaysian companies in the states of Johor, Kedah, Kelantan, Melaka, Negeri Sembilan, Perak, Pulau Pinang, Selangor and the federal territory of Kuala Lumpur were surveyed in the year 2019. This paper presents results on eight of the seventeen sustainable development goals, namely, the goals to end poverty, end hunger, ensure healthy lives, ensure inclusive education, ensure access to sustainable energy, ensure sustainable development, take urgent actions to combat climate change, protect terrestrial ecosystem, and strengthen global partnerships to achieve goals. Results based on descriptive analysis show that most of the surveyed firms have yet to achieve progress in the listed sustainable development goals. As Malaysia is a developing country, these results may be consistent with the country’s economic development path that prioritise the attainment of higher income growth.